Araucaria Araucana thermoplastic starch nanocomposite films reinforced with nanocellulose - Nazrin A.; Norfarhana A.S.; Ilyas R.A.; Sapuan S.M.; Khalina A.; Syafiq R.M.O.; Huzaifah M.R.M.; Azmi A.; Khoo P.S.; Nordin A.H.; Hawanis H.S.N.; Hassan S.A. (De Gruyter, 2024)
Araucaria Araucana starch is a raw material with proven potential in obtaining biodegradable polymers. Plasticization improves the flexibility characteristics of starch-based films, however, they still tend to have low tensile strength and high hydrophilicity. The addition of nanocellulose is a technique to improve these characteristics. In this paper, the effects of adding different sources and concentrations of nanocellulose (NC) on the properties of thermoplastic Araucaria Araucana films are addressed. One can highlight, the main effects are the increase of tensile strength and transparency of the films along with the reduction of water vapor permeability and water solubility. Further studies involving the reinforcement of Araucaria Araucana starch and nanocellulose should be conducted to overcome the lack of information. 2023 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.